Startups and Local Social Capital in the Municipalities of Sweden - Hans Westlund; Johan P. Larsson; Amy Olsson (European Regional Science Association (ERSA), 2012)
This paper contains one of the first empirical attempts to investigate the influence of local Entrepreneurial Social Capital on startup propensity. We use a unique database including not only total startups, but data on startups divided in six branches to study the impact of Entrepreneurial social capital on startups per capita. Analyses are performed on all municipalities as well as by municipality type (urban or rural). Entrepreneurial social capital, measured by local firms' assessment of local publics' attitudes to entrepreneurship seem to exert a positive and significant influence on local startup rates in both urban and rural municipalities in Sweden. When startups are being divided in six branch groups, entrepreneurial social capital keeps its significance for all branches in rural areas, while it stays significant for two of the groups in urban areas. Thus, social capital seems to have a broader and more general impact on startup rates in rural areas.
Keywords: 330; Entrepreneurship; Startups; Entrepreneurial social capital